Handbook of the arts in qualitative research: Perspectives, methodologies, examples, and issues - Knowles, Gary J.; Cole, Ardra L. (Sage Publications, 2008)
"This work's quality, diversity, and breadth of coverage make it a valuable resource for collections concerned with qualitative research in a broad range of disciplines. Highly recommended." G.R. Walden, CHOICEThe Handbook of the Arts in Qualitative Inquiry: Perspectives, Methodologies, Examples, and Issues represents an unfolding and expanding orientation to qualitative social science research that draws inspiration, concepts, processes, and representational forms from the arts. In this defining work, J. Gary Knowles and Ardra L. Cole bring together the top scholars in qualitative methods to provide a comprehensive overview of the past, present, and future of arts-based research. This Handbook provides an accessible and stimulating collection of theoretical arguments and illustrative examples that delineate the role of the arts in qualitative social science research. Key Features Defines and explores the role of the arts in qualitative social science research: The Handbook presents an analysis of classic and emerging methodologies and approaches that employs the arts in the qualitative research process.Brings together a unique group of scholars: Offering diverse perspectives, contributors to this volume represent a wide range of disciplines including the humanities, media and communication, anthropology, sociology, psychology, women's studies, education, social work, nursing, and health and medicine.Offers comprehensive coverage of the genres employed by qualitative researchers: Scholars use multiple ways to advance knowledge including literary forms, performance, visual art, various types of media, narrative, folk art, and more.Articulates challenges inherent in alternative methodologies: This volume discusses the issues and challenges faced when employing art in research including ethical issues, academic merit issues, and even funding issues.Intended Audience This is an essential resource for any scholar interested in qualitative research, as well as a critical resource for all academic and public libraries. The bringing together of the arts and qualitative inquiry is changing the face of social science research. The increasing shift toward arts-based research has raised complex questions, such as how to evaluate its quality and even whether distinctions exist between what is art and what is research. In this defining work, Gary Knowles and Ardra Cole bring together the top scholars in qualitative methods to provide a comprehensive overview of where arts-based research has come, and where it is going. Through various categories of art and art-based research - namely epistemological, historical, methodological, thematic - will address all the significant issues of conceiving and conducting arts-based or arts-informed research in the social sciences and humanities, as well as the challenges of composing final representations of the research.